I made a picture for any of you to look at, so long as you graph it by computer or graphing utility first. This bunch of mess is beautiful. It's a graphical version of the Sierpinski triangle, but I used only circles to achieve what appear to be triangles. You'll notice some straight lines forming rectangles. These serve to border, or "frame" my art. To see the picture, view all equations in the same window... In other words, let them overlap. Enjoy.

let sqrt(x) be the square root of x. Stuff like 26^2 means 26 squared (26 times 26)

1) x^2+y^2=26^2

2) x^2+(y+26)^2=26^2

3) x^2+y^2=13^2

4) x^2+(y+13)^2=(13/2)^2

5) (x-13sqrt(3))^2+(y+13)^2=26^2

6) (x-13sqrt(3))^2+(y-13)^2=26^2

7) x^2+(y-26)^2=26^2

8) (x+13sqrt(3))^2+(y-13)^2=26^2

9) (x+13sqrt(3))^2+(y+13)^2=26^2

10) (x-(13sqrt(3))/2)^2+(y-(13/2))^2=(13/2)^2

11) (x+(13sqrt(3))/2)^2+(y-(13/2))^2=(13/2)^2

12) (x+(39sqrt(3))/4)^2+(y-(39/4))^2=(13/4)^2

13) (x-(39sqrt(3))/4)^2+(y-(39/4))^2=(13/4)^2

14) (x+(13sqrt(3))/4)^2+(y-(39/4))^2=(13/4)^2

15) (x-(13sqrt(3))/4)^2+(y-(39/4))^2=(13/4)^2

16) x^2+(y+(39/4))^2=(13/4)^2

17) (x-(13sqrt(3))/2)^2+y^2=(13/4)^2

18) (x+(13sqrt(3))/2)^2+y^2=(13/4)^2

19) (x+(13sqrt(3))/4)^2+(y+(39/4))^2=(13/4)^2

20) (x-(13sqrt(3))/4)^2+(y+(39/4))^2=(13/4)^2

21) (x+(91sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

22) x^2+(y+(91/4))^2=(13/8)^2

23) (x-(91sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

24) (x+(65sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

25) (x+(39sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

26) (x+(13sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

27) (x-(13sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

28) (x-(39sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

29) (x-(65sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

30) (x+(13sqrt(3))/4)^2+(y-(13/2))^2=(13/8)^2

31) (x+(39sqrt(3))/4)^2+(y-(13/2))^2=(13/8)^2

32) (x-(13sqrt(3))/4)^2+(y-(13/2))^2=(13/8)^2

33) (x-(39sqrt(3))/4)^2+(y-(13/2))^2=(13/8)^2

34) (x+(13sqrt(3))/2)^2+(y+(13/4))^2=(13/8)^2

35) (x-(13sqrt(3))/2)^2+(y+(13/4))^2=(13/8)^2

36) (x+(65sqrt(3))/8)^2+(y-(13/8))^2=(13/8)^2

37) (x-(65sqrt(3))/8)^2+(y-(13/8))^2=(13/8)^2

38) (x+(39sqrt(3))/8)^2+(y-(13/8))^2=(13/8)^2

39) (x-(39sqrt(3))/8)^2+(y+(65/8))^2=(13/8)^2

40) (x+(39sqrt(3))/8)^2+(y+(65/8))^2=(13/8)^2

41) (x-(39sqrt(3))/8)^2+(y-(13/8))^2=(13/8)^2

42) (x+(13sqrt(3))/8)^2+(y+(65/8))^2=(13/8)^2

43) (x-(13sqrt(3))/8)^2+(y+(65/8))^2=(13/8)^2

44) (x+(13sqrt(3))/4)^2+(y+13)^2=(13/8)^2

45) (x-(13sqrt(3))/4)^2+(y+13)^2=(13/8)^2

46) (x+(13sqrt(3))/8)^2+(y+(143/8))^2=(13/8)^2

47) (x-(13sqrt(3))/8)^2+(y+(143/8))^2=(13/8)^2

48) x^2+y^2=29^2

49) x^2+y^2=33^2

50) x^2+y^2=39^2

51) x^2+y^2=41^2

52) x^2+y^2=43^2

53) x^2+y^2=45^2

54) x^2+y^2=47^2

55) x^2+y^2=52^2

56) y=44

57) y=-44

58) y=30

59) y=-30

60) y=36

61) y=-36

62) x=48

63) x=-48

64) x=54

65) x=-54

66) x= 62

67) x=-62

Christopher

let sqrt(x) be the square root of x. Stuff like 26^2 means 26 squared (26 times 26)

1) x^2+y^2=26^2

2) x^2+(y+26)^2=26^2

3) x^2+y^2=13^2

4) x^2+(y+13)^2=(13/2)^2

5) (x-13sqrt(3))^2+(y+13)^2=26^2

6) (x-13sqrt(3))^2+(y-13)^2=26^2

7) x^2+(y-26)^2=26^2

8) (x+13sqrt(3))^2+(y-13)^2=26^2

9) (x+13sqrt(3))^2+(y+13)^2=26^2

10) (x-(13sqrt(3))/2)^2+(y-(13/2))^2=(13/2)^2

11) (x+(13sqrt(3))/2)^2+(y-(13/2))^2=(13/2)^2

12) (x+(39sqrt(3))/4)^2+(y-(39/4))^2=(13/4)^2

13) (x-(39sqrt(3))/4)^2+(y-(39/4))^2=(13/4)^2

14) (x+(13sqrt(3))/4)^2+(y-(39/4))^2=(13/4)^2

15) (x-(13sqrt(3))/4)^2+(y-(39/4))^2=(13/4)^2

16) x^2+(y+(39/4))^2=(13/4)^2

17) (x-(13sqrt(3))/2)^2+y^2=(13/4)^2

18) (x+(13sqrt(3))/2)^2+y^2=(13/4)^2

19) (x+(13sqrt(3))/4)^2+(y+(39/4))^2=(13/4)^2

20) (x-(13sqrt(3))/4)^2+(y+(39/4))^2=(13/4)^2

21) (x+(91sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

22) x^2+(y+(91/4))^2=(13/8)^2

23) (x-(91sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

24) (x+(65sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

25) (x+(39sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

26) (x+(13sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

27) (x-(13sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

28) (x-(39sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

29) (x-(65sqrt(3))/8)^2+(y-(91/8))^2=(13/8)^2

30) (x+(13sqrt(3))/4)^2+(y-(13/2))^2=(13/8)^2

31) (x+(39sqrt(3))/4)^2+(y-(13/2))^2=(13/8)^2

32) (x-(13sqrt(3))/4)^2+(y-(13/2))^2=(13/8)^2

33) (x-(39sqrt(3))/4)^2+(y-(13/2))^2=(13/8)^2

34) (x+(13sqrt(3))/2)^2+(y+(13/4))^2=(13/8)^2

35) (x-(13sqrt(3))/2)^2+(y+(13/4))^2=(13/8)^2

36) (x+(65sqrt(3))/8)^2+(y-(13/8))^2=(13/8)^2

37) (x-(65sqrt(3))/8)^2+(y-(13/8))^2=(13/8)^2

38) (x+(39sqrt(3))/8)^2+(y-(13/8))^2=(13/8)^2

39) (x-(39sqrt(3))/8)^2+(y+(65/8))^2=(13/8)^2

40) (x+(39sqrt(3))/8)^2+(y+(65/8))^2=(13/8)^2

41) (x-(39sqrt(3))/8)^2+(y-(13/8))^2=(13/8)^2

42) (x+(13sqrt(3))/8)^2+(y+(65/8))^2=(13/8)^2

43) (x-(13sqrt(3))/8)^2+(y+(65/8))^2=(13/8)^2

44) (x+(13sqrt(3))/4)^2+(y+13)^2=(13/8)^2

45) (x-(13sqrt(3))/4)^2+(y+13)^2=(13/8)^2

46) (x+(13sqrt(3))/8)^2+(y+(143/8))^2=(13/8)^2

47) (x-(13sqrt(3))/8)^2+(y+(143/8))^2=(13/8)^2

48) x^2+y^2=29^2

49) x^2+y^2=33^2

50) x^2+y^2=39^2

51) x^2+y^2=41^2

52) x^2+y^2=43^2

53) x^2+y^2=45^2

54) x^2+y^2=47^2

55) x^2+y^2=52^2

56) y=44

57) y=-44

58) y=30

59) y=-30

60) y=36

61) y=-36

62) x=48

63) x=-48

64) x=54

65) x=-54

66) x= 62

67) x=-62

Christopher

Subscribe, Follow, Interact, Comment and change YOUR community!

Email at Jpay.com using Christopher Havens # 349034

Or by Mail:

Christopher Havens # 349034

MCC-TRU

PO Box 888

_{}^{}
## No comments:

## Post a Comment

Please leave comments or suggestions so we can continue to interact with you. All comments will be monitored and responded to. We love your interactions with us.